1991
DOI: 10.1210/jcem-73-4-727
|View full text |Cite
|
Sign up to set email alerts
|

Variables Controlling the Secretion of Insulin-Like Growth Factor Binding Protein-2 in Normal Human Subjects*

Abstract: Insulin-like growth factor binding protein-2 (IGFBP-2) is one of a family of IGFBPs that are present in extracellular fluids, and binds both IGF-II and IGF-I with high affinity. These studies were conducted to determine the nutritional and hormonal variables that regulate plasma IGFBP-2 concentrations in humans. The mean plasma IGFBP-2 concentration for 38 normal adult subjects was 150 +/- 61 micrograms/L and was 4.7-fold greater than their mean fasting IGFBP-1 value. Mean IGFBP-2 values in cord sera of 26 nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
104
2
1

Year Published

1994
1994
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(117 citation statements)
references
References 23 publications
(41 reference statements)
10
104
2
1
Order By: Relevance
“…34 Several reports have shown that IGFBP-2 is differentially regulated by GH and IGF-1. 12,34 Administration of GH causes a reduction in IGFBP-2, while the serum concentration of IGFBP-2 is high in states of GH de®ciency. 34 In normal adults, the infusion of IGF-1 results in suppression of GH and an increase in IGFBP-2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…34 Several reports have shown that IGFBP-2 is differentially regulated by GH and IGF-1. 12,34 Administration of GH causes a reduction in IGFBP-2, while the serum concentration of IGFBP-2 is high in states of GH de®ciency. 34 In normal adults, the infusion of IGF-1 results in suppression of GH and an increase in IGFBP-2.…”
Section: Discussionmentioning
confidence: 99%
“…12,34 Administration of GH causes a reduction in IGFBP-2, while the serum concentration of IGFBP-2 is high in states of GH de®ciency. 34 In normal adults, the infusion of IGF-1 results in suppression of GH and an increase in IGFBP-2. 38 The dissociation of the effect of GH and IGF-1 in regulating IGFBP-2 suggests that IGFBP-2 and the ratio of IGFBP-2 to IGF-1 may be useful in detecting GH de®ciency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Langford and Miell [29] reported that cord IGF-I negatively correlated with IGFBP-2, this was not the case in the present study with diabetic patients. It appears that a change in glucose metabolism has little effect, if any, on IGFBP-2 production [39].…”
Section: Relation Between Birth Weight and Serum Concentrations Of Fementioning
confidence: 99%